Loan Sales and Borrowers' Accounting Conservatism1. (1st August 2018) - Deng, Saiying; Li, Yutao; Lobo, Gerald J.; Shao, Pei
ABSTRACT: We examine whether initial loan sales in the secondary loan market relate to borrowing firms' accounting conservatism. We find that borrowing firms exhibit a significant decline in accounting conservatism after the initial loan sales. We show that the decline in borrower conservatism is more pronounced for firms that borrow from lenders with lower monitoring incentives and for firms that have lower incentives to supply conservatism. The baseline results are robust to a battery of sensitivity tests. Collectively, we provide corroborative evidence that lead lenders' monitoring incentives enforce accounting conservatism in the private debt market, and that lead lenders play a more prominent role than secondary loan market participants in shaping corporate (conservative) reporting.